THE INFLUENCE OF CAPITAL STRUCTURE ON PROFITABILITY AND FIRM VALUE (A Study on Food and Beverage Companies listed in Indonesia Stock Exchange 2010-2012 period) - Shinta D. Manurung (Fakultas Ilmu Administrasi Universitas Brawijaya, 2014)
This research is conducted to enhance the knowledge about capital structure, profitability, and firm value. In this research, the capital structure is represented by three indicators: Debt Ratio, Debt Equity Ratio, and Long Term Debt to Equity. Profitability is examined by Return on Asset, Return on Equity and Net Profit Margin, while firm value is proxy by Book Value, Price to Book Value, and Closing Price. Using Partial Least Square Method, this study finds that all indicators are useful to measure the latent variables. While in the analysis of structural model or inner model, the result supports Hypothesis 1 that capital structure has negatively significant influence on firm value. The higher the debts that firms employed, the lower its values. This study also supports Hypothesis 2 that capital structure influences the profitability significantly. This indicates that firms with high capital structures will have a decrease in profit. The result of the research also supports Hypothesis 3 that profitability influences the firm values positively. It means that higher profitability of a firm will result in a higher firm value. Key words: Capital Structure, Profitability, Firm Value